Mathematical Analysis of Cholera Transmission Incorporating Media Coverage - Hassan Muhammad; Auwal Abdullahi (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Cholera is an acute gastrointestinal disease caused by the bacterium Vibrio cholerae and is primarily transmitted through the consumption of food or water contaminated with fecal matter from infected individuals. Given its rapid transmission, widespread occurrence, and potentially fatal consequences, effective prevention and control require integrated interventions, including vaccination, water chlorination, and appropriate treatment. This study aims to develop and analyze a mathematical model of cholera transmission that incorporates the effect of media coverage on disease dynamics. The model was formulated using a system of differential equations, and its stability properties were examined by deriving the basic reproduction number, (R0), through the next-generation matrix method. Numerical simulations were subsequently conducted to assess the influence of media awareness on cholera transmission. The findings indicate that increased media awareness substantially reduces the number of cholera cases, demonstrating the important role of public health communication in limiting disease spread. These results suggest that integrating media campaigns with established cholera prevention and control measures can strengthen efforts to reduce outbreaks. This study contributes a mathematical framework for understanding the role of media coverage in cholera transmission dynamics and provides practical insights for incorporating public health communication into disease-control strategies.